2022
DOI: 10.1021/acs.iecr.2c01630
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Robust and High Resilient Polythiophene Conductive Polyamides Fibers Based on Tannic Acid Modification

Abstract: In this work, conductive polyamide fibers were successfully prepared through polymerization of thiophene on the surface of polyamide fibers based on fiber pretreatment and surface activation modification. Sulfuric acid was utilized to roughen the polyamide fibers to increase the activity. Tannic acid (TA) was oxidized and grafted onto the roughened polyamide fibers to convert the inert surface into a highly adhesive tannic acid surface, thus improving the fastness of polythiophene on fiber surface. The effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…As shown in Figure b, the peak at 1713 cm –1 indicates the presence of carboxylic acid vibrations on the TA molecule. Furthermore, a peak at 1035 cm –1 was observed due to the C–N stretching vibrations resulting from the Michael addition reaction between TA and the amino groups. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure b, the peak at 1713 cm –1 indicates the presence of carboxylic acid vibrations on the TA molecule. Furthermore, a peak at 1035 cm –1 was observed due to the C–N stretching vibrations resulting from the Michael addition reaction between TA and the amino groups. , …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a peak at 1035 cm −1 was observed due to the C−N stretching vibrations resulting from the Michael addition reaction between TA and the amino groups. 39,40 XPS analysis revealed that the ANFs and TA/ANF films primarily consisted of carbon (C), nitrogen (N), and oxygen (O) elements (Figure 3c and Table S2). From the slight change in the percentage of the N element, it can be concluded that most of the TA molecules were washed away.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%